Color Doppler Sonographic Dynamic Tissue Perfusion Measurement Demonstrates Significantly Reduced Cortical Perfusion in Children with Diabetes Mellitus Type 1 without Microalbuminuria and Apparently Healthy Kidneys - Scholbach, T. M.; Vogel, C.; Bergner, N. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Motivation: With respect to the devastating consequences of the increasing prevalence of diabetes mellitus, the main reason for end stage renal disease and dialysis in industrialized countries, and the very limited diagnostic and therapeutic possibilities to predict, monitor and prevent diabetic nephropathy (DN), new concepts for early recognition and quantification of the prevailing microvascular changes in DN are urgently needed.Materials and Methods: We present the first study of renal cortical tissue perfusion measurement by means of standardized color Doppler sonographic videos evaluated with the PixelFlux software 1 for Dynamic Tissue Perfusion Measurement (DTPM) in 92 patients with DM1 without MA compared to 71 healthy probands.Results: DTPM reveals a highly significant diminution of cortical perfusion in patients with DM1 compared to healthy probands by 31 %, most pronounced in the distal hemicortex (reduction by 50 %) compared to 21 % within the proximal hemicortex.Conclusion: Thus, DTPM offers a novel means of numerically describing the state of the renal microvasculature in DM in a patient-friendly, non-invasive, non-ionizing manner.
Keywords: ultrasound color Doppler; dynamic tissue perfusion measurement; kidney; diabetes mellitus